2011
DOI: 10.1128/aem.01968-10
|View full text |Cite
|
Sign up to set email alerts
|

Volatile-Mediated Killing of Arabidopsis thaliana by Bacteria Is Mainly Due to Hydrogen Cyanide

Abstract: The volatile-mediated impact of bacteria on plant growth is well documented, and contrasting effects have been reported ranging from 6-fold plant promotion to plant killing. However, very little is known about the identity of the compounds responsible for these effects or the mechanisms involved in plant growth alteration. We hypothesized that hydrogen cyanide (HCN) is a major factor accounting for the observed volatile-mediated toxicity of some strains. Using a collection of environmental and clinical strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(116 citation statements)
references
References 55 publications
2
108
1
Order By: Relevance
“…Contrary to the role of HCN as abiocontrol agent, several researchers concluded that HCN is hardly a universal biocontrol agent and even caused phytotoxic effects in most in vitro experiments (Alström and Burns, 1989;Pal et al, 2000;Kremer and Souissi, 2001;Rudrappa et al, 2008;Blom et al, 2011). In a recent study by Rijavec and Lapanje (2016) have shown that there is no correlation between the amount of HCN produced by a particular strain and its ability to inhibit the growth of phytopathogenic bacteria or fungi.…”
Section: Stress (Salt and Ph) Tolerant Pgprmentioning
confidence: 99%
“…Contrary to the role of HCN as abiocontrol agent, several researchers concluded that HCN is hardly a universal biocontrol agent and even caused phytotoxic effects in most in vitro experiments (Alström and Burns, 1989;Pal et al, 2000;Kremer and Souissi, 2001;Rudrappa et al, 2008;Blom et al, 2011). In a recent study by Rijavec and Lapanje (2016) have shown that there is no correlation between the amount of HCN produced by a particular strain and its ability to inhibit the growth of phytopathogenic bacteria or fungi.…”
Section: Stress (Salt and Ph) Tolerant Pgprmentioning
confidence: 99%
“…The PGP effects were largely attributed to two volatiles, namely, 3-hydroxybutan-2-one (acetoin) and 2,3-butanediol. Several other studies have examined bacterial bioactive volatile compounds that promote or suppress plant growth (Farag et al, 2006;Splivallo et al, 2007;Vespermann et al, 2007;Kai et al, , 2010GutiĂ©rrez-Luna et al, 2010;Zou et al, 2010;Blom et al, 2011aBlom et al, , 2011bVelazquez-Becerra et al, 2011;Weise et al, 2012;Yu and Lee, 2013), but the underlying mechanisms of these effects remain largely unknown (Wenke et al, 2012b). Profiling studies in Arabidopsis seedlings provided the first insights into changes in the transcriptome and proteome elicited by exposure to bacterial VOCs (Zhang et al, 2007;Kwon et al, 2010) and revealed the importance of hormone signaling, particularly that of indole-3-acetic acid and abscisic acid (Zhang et al, 2007(Zhang et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The research carried out to understand the nature of this volatile-mediated interaction of bacteria with plants and with other bacteria has focused so far on model organisms (e.g., Arabidopsis thaliana and Escherichia coli) and has enabled identification of some of the active compounds involved in the respective interactions, such as indole, 2,3-butanediol, dimethyl disulfide, hydrogen sulfide, and ammonia. The research on model organisms has also contributed to understanding of the mechanisms underlying the observed phenotypic changes of increased (13)(14)(15) or decreased (16,17) plant biomass and increased antibiotic resistance in bacteria (2)(3)(4)18).…”
mentioning
confidence: 99%